Apert syndrome (Acrocephalosyndactyly): a case report - Saritha, S.; Supriya, Sumangala, G.; Kumar, M. Praveen (International Journal of Research in Medical Sciences, 2017)
Apert syndrome is named for the French physician. Eugene Apert in 1906 described the syndrome acrocephalosyndactylia. It is a rare autosomal dominant disorder characterized by craniosynostosis, craniofacial anomalies, and severe symmetrical syndactyly of the hands and feet (i.e. cutaneous and bony fusion refers to webbing of fingers and toes). Apert syndrome is characterized by the premature fusion of certain skull bones (craniosynostosis). This early fusion prevents the skull from growing normally and affects the shape of the head and face. In addition, a varied number of fingers and toes are fused together (syndactyly). Most cases of Apert syndrome are sporadic, may result from new mutations in the gene. The purpose of this paper is to report a case of Apert syndrome in a female fetus of 30 weeks with asymmetrical skull confirmed by prenatal ultrasonography. Pregnancy was terminated and fetus was submitted for detailed autopsy in anatomy dissection hall. The findings and review of literature were presented in this article.